MASALAH KESEHATAN PENYINTAS GEMPA DAN TSUNAMI DI DONGGALA, SIGI DAN PALU, SULAWESI TENGAH - Bambang Wiseno (LPPM - STIKES Pemkab Jombang, 2019)
ABSTRACT Indonesia is an archipelago country located on the Ring of Fire has experienced many natural disasters. On September 28, 2018 a earthquake with magnitude 7.7 caused a tsunami in Donggala, Sigi and Palu in Province of Sulawesi Tengah. Declared a national disaster, the government and many humanitarian organizations (NGOs) domestic and foreign, who are help to deal the problems caused. For this matter, writers is a llecturer and one’s of memberf the NGO Indonesian Red Crescent Society (BSMI) after two weeks of disaster have conduct health services and provide assistance to alleviate the bio, psychological, socio and cultural burden. Nearly 845 residents checked their health conditions at health posts created. Health problems found were diarrhea and digestive disorders, respiratory tract infections, hypertension, skin diseases and various post-traumatic syndroma disorder problems. Based on the literature and these findings it can be concluded, the problems needs more attention in the handling and prevention, and helper / voluntere should be readiness to provide mental health / psychosocial support after the disaster.